The temptation of forgiveness [large type] - Leon, Donna (Leon, Donna. Commissario Guido Brunetti mystery., 2018)
In the twenty-seventh novel in Donna Leon's bestselling mystery series, a suspicious accident leads Commissario Guido Brunetti to uncover a longstanding scam with disturbing unintended consequences.